2003
DOI: 10.1074/jbc.m305485200
|View full text |Cite
|
Sign up to set email alerts
|

A Mutated Form of Steroidogenic Factor 1 (SF-1 G35E) That Causes Sex Reversal in Humans Fails to Synergize with Transcription Factor GATA-4

Abstract: Steroidogenic factor 1 (SF-1) is a transcription factor belonging to the nuclear receptor superfamily. SF-1 regulates the expression of many genes involved in reproduction, steroidogenesis, and sexual differentiation. An important SF-1 target for male sexual differentiation is the gene encoding the Mü llerian-inhibiting substance hormone that induces regression of the Mü llerian ducts in the developing male embryo. Not long ago, a mutation (G35E) in the human SF-1 gene was identified as the cause of sex revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…In contrast to the recessive SF1 mutations, impairment of TESCO activation by G35E (which is known to cause autosomal-dominant DSD; ref. 20) remained even with coexpression of SRY or SOX-9, and similar results were obtained in CHO cells ( Figure 3B and Supplemental Figure 3). This qualitative difference between recessive mutations and a severe dominant SF1 mutation was not (7), showing the DNA-binding domain bound to its target sequence in the inhibin α subunit promoter.…”
Section: Resultssupporting
confidence: 84%
“…In contrast to the recessive SF1 mutations, impairment of TESCO activation by G35E (which is known to cause autosomal-dominant DSD; ref. 20) remained even with coexpression of SRY or SOX-9, and similar results were obtained in CHO cells ( Figure 3B and Supplemental Figure 3). This qualitative difference between recessive mutations and a severe dominant SF1 mutation was not (7), showing the DNA-binding domain bound to its target sequence in the inhibin α subunit promoter.…”
Section: Resultssupporting
confidence: 84%
“…GATA4 binds to NR5A1 to synergistically enhance the expression of AMH by regulating its promoter (24). We studied the ability of p.Gly221Arg mutant to retain this synergy.…”
Section: Gata4 Pgly221arg Does Not Synergize With Nr5a1 To Stimulatementioning
confidence: 99%
“…GATA4 functionally interacts with NR5A1 in primary Sertoli cell cultures to positively regulate the expression of AMH, through two complementary mechanisms, either by binding to its site on the AMH promoter or by direct interaction with NR5A1 when either NR5A1 alone or both GATA4 and NR5A1 are bound to their respective sites on the AMH promoter (18). Mutations in NR5A1 may cause 46,XY DSD through a lack of appropriate interaction with GATA4 (24). No mutations in GATA4 have been reported in association with human cases of DSD.…”
mentioning
confidence: 99%
“…There is also co-operation between GATA-4 and SF-1 to regulate the expression of AMH (anti-Müllerian hormone) ). The lack of co-operation of these two substances could be the reason for some cases of abnormal sex differentiation in humans (Tremblay and Viger 2003). Recently it has also been found that the human HSD3B2 promoter is activated by GATA transcription factors (Martin et al 2005), presumably by GATA-6 (Bassett et al 2005).…”
Section: Page 4 Of 24mentioning
confidence: 99%